Active tectonics and paleo-earthquakes in north Yumu Shan, northern Tibetan Plateau: Insights from structural analysis and radiocarbon dating - Wang, Ye; Chen, Xuanhua; He, Chengguang; Xiao, Yongjun; Shao, Zhaogang; Han, Jian’en; Li, Bing; Zhang, Yiping; Ding, Weicui; Xu, Shenglin; Han, Lele (Frontiers in Earth Science, 2023)
The Yumu Shan is located at the northern margin of the Tibetan Plateau in northwest China. It is characterized by the development of several northeastward-protruding arcuate geomorphic bulge belts on its north slope. These bulge belts are distributed along the Wutongquan spring, the ancient Camel City, and the Xiaogengzi area, and south to Gaotai City in the Hexi Corridor. In this study, our detailed field mapping and structural analysis reveal northeastward active anticline folding along the curved bulge belts and related lacustrine sediments in their hinterlands. Radiocarbon dating of plant charcoal samples from lacustrine sedimentary layers yields a 14C age of AD 178 ± 42. This age is close to the time of the 180AD/Ms7.5 earthquake at Biaoshi City (i.e., the ancient Zhangye City) during the Eastern Han Dynasty. The similarity between seismic events and sedimentary age leads us to infer that the charcoal in the lacustrine layer records a major flood event related to the Biaoshi earthquake. We propose a fault-related fold model for the formation of the arcuate bulge belts and related sediments. First, a series of historical earthquake activities in the Holocene, especially the 180AD/Ms7.5 Biaoshi earthquake, may have led to active blind thrust faulting in the northern margin of the plateau. Then, blind thrusting may have resulted in fault-related anticline folding, causing the formation of geomorphic bulges. The latter acts as a flood-retaining dam, resulting in hinterland deposition of lacustrine sediments. For this reason, we suggest that seismogenic blind thrust faulting is responsible for the uplift and northward growth of the Tibetan Plateau. As the northernmost blind thrust in this area, the Xiaogengzi Fault could be considered the North Boundary Thrust (NBT), which defines exactly the northern margin of the plateau.